2018
DOI: 10.1111/aeq.12244
|View full text |Cite
|
Sign up to set email alerts
|

The Cultural Production of the “Disabled” Person: Constructing Difference in Bhutanese Schools

Abstract: The Himalayan country of Bhutan has witnessed monumental social and cultural changes in only the last fifty years with the implementation and institutionalization of mass secular schooling. This “modern” schooling has also served to newly sort, produce, and construct “disabled” persons. Through a year of ethnographic fieldwork, I explored this construction of disability through the institution of schooling and have organized these observations into four forms: physical, pedagogical, curricular, and linguistic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…It seems that these issues are complex and perplexed by biological, psychological, cultural, and socio-political factors. Socio-cultural perspectives on disability studies argue that societal structures themselves construct disability and shape participants (Schuelka 2018) and culture has played a key role in how the parents experienced and shaped their understanding of autism. The power of socio-cultural perspectives can be observed in how religion can have a positive impact in some cultures and help the parents cope with having a child with autism (Luong et al 2009), and furthermore, religion (Munroe et al 2016) and cultural traditional beliefs can provide models for explaining the cause for autism (Ijalba 2015).…”
Section: Multilanguagementioning
confidence: 99%
“…It seems that these issues are complex and perplexed by biological, psychological, cultural, and socio-political factors. Socio-cultural perspectives on disability studies argue that societal structures themselves construct disability and shape participants (Schuelka 2018) and culture has played a key role in how the parents experienced and shaped their understanding of autism. The power of socio-cultural perspectives can be observed in how religion can have a positive impact in some cultures and help the parents cope with having a child with autism (Luong et al 2009), and furthermore, religion (Munroe et al 2016) and cultural traditional beliefs can provide models for explaining the cause for autism (Ijalba 2015).…”
Section: Multilanguagementioning
confidence: 99%
“…This was not entirely surprising to us, given that earlier research in the Bhutanese schooling context indicated the Page 25 of 34 existence of negative role modelling -despite the introduction of GNH values and principles for education -in the form of impolite and rude use of language by the teachers in the classroom (Kezang Sherab 2013). Concepts such as 'student well-being' are very new to the Bhutanese education system (Sangay Jamtsho 2015) and a view of behaviourism and punishment as appropriate educational measures -even in the form of physical abuse -is still widespread despite being officially banned (Schuelka 2018). By saying this, we are not explicitly judging, or blaming, Bhutanese teachers, nor are we putting English teachers on a pedestal.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Schuelka (2015) found that in Third, our findings in Myanmar suggest that it is not the attitudes of people themselves that conceptualise disability in a society, but it is the socio-cultural nature of the structures, systems, and institutions in which they inhabit. A socio-cultural perspective on disability advances that societal structures themselves construct disability and shape participants (McDermott and Varenne, 1995;Schuelka, 2018).…”
Section: Formatted: Line Spacing: Singlementioning
confidence: 99%